2017
DOI: 10.1039/c6fo01164k
|View full text |Cite
|
Sign up to set email alerts
|

DNA and BSA damage inhibitory activities, and anti-acetylcholinesterase, anti-porcine α-amylase and antioxidant properties of Dolichos lablab beans

Abstract: The underutilized Kenyan variety of Dolichos lablab bean seeds serve as a good source of natural antioxidants, which can probably be effective in reducing the risk of occurrence of several diseases. This study was undertaken for the first time to address the limited knowledge regarding the antioxidant activities of lablab beans. Moreover, their DNA damage inhibitory activity, bovine serum albumin (BSA) damage inhibitory activity, and the inhibition of acetylcholinesterase and porcine α-amylase were also invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…Beneficial effects of antioxidants in foods are due to their ability to destroy reactive, food-damaging free radicals, thus enhancing nutritional quality and safety [ 41 , 42 ]. Beneficial effects of antioxidants in vivo are due to their ability to destroy reactive oxygen species (ROS) that damage DNA and essential enzymes [ 43 ]. Since inflammation is a risk factor for aging [ 44 ], arthritis [ 45 ], asthma in mice [ 46 ] and in children [ 47 ], cancer [ 48 ], as well as diabetes and obesity [ 49 ], the results of the present study, and the cited findings by other investigators, suggest that purpurin has the potential to protect food against oxidative damage and ameliorate chronic diseases in vivo, analogous to the protective effects of mushroom polysaccharides described elsewhere [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial effects of antioxidants in foods are due to their ability to destroy reactive, food-damaging free radicals, thus enhancing nutritional quality and safety [ 41 , 42 ]. Beneficial effects of antioxidants in vivo are due to their ability to destroy reactive oxygen species (ROS) that damage DNA and essential enzymes [ 43 ]. Since inflammation is a risk factor for aging [ 44 ], arthritis [ 45 ], asthma in mice [ 46 ] and in children [ 47 ], cancer [ 48 ], as well as diabetes and obesity [ 49 ], the results of the present study, and the cited findings by other investigators, suggest that purpurin has the potential to protect food against oxidative damage and ameliorate chronic diseases in vivo, analogous to the protective effects of mushroom polysaccharides described elsewhere [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…DPPH · is a fairly stable free radical that accepts hydrogen radical or electron, thus becoming a stable diamagnetic molecule. It has been widely used to assess the activity of natural antioxidants against free radicals in-vitro 17 . The results of the current investigation indicated that, based on the concentrations used, VGSE significantly (p < 0.05) inhibited DPPH · radical activity as shown in Table 2 for IC 50 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HPLC-analysis (RP-HPLC) was performed as described by Habib et al 17 . In brief, with a 1525 Binary HPLC pump (Waters, Milford, MA, USA) separation module equipped with a 717 plus auto-sampler (Waters, Milford, MA, USA), 2487 dual UV.…”
Section: Methodsmentioning
confidence: 99%
“…The lablab bean seeds were ground into flour and extracted with water, methanol/water (50/50) or absolute methanol. The results showed that the aqueous methanolic extract was the most potent with 3.06% AChE inhibition when compared to 1.09% for the absolute methanol extract and 0% for the water extract [30]. Correlation analysis indicated 0.985 relationship between the AChE‐inhibitory and total flavonoids of the aqueous methanolic extract while a similar but negative value was obtained for the total phenols.…”
Section: Food‐derived Polyphenolic Compoundsmentioning
confidence: 99%